MITHRA – multiparametric MR/CT image adapted brachytherapy (MR/CT-IABT) in anal canal cancer: a feasibility study - Tagliaferri, Luca; Manfrida, Stefania; Barbaro, Brunella; Colangione, Maria Maddalena; Masiello, Valeria; Mattiucci, Gian Carlo; Placidi, Elisa; Autorino, Rosa; Gambacorta, Maria; Chiesa, Silvia; Mantini, Giovanna; Kovács, György; et al. (Journal of Contemporary Brachytherapy, 2015)
Purpose : The aim of this study is to test a novel multiparametric imaging guided procedure for high-dose- rate brachytherapy in anal canal cancer, in order to evaluate the feasibility and safety. Material and methods : For this analysis, we considered all consecutive patients who underwent magnetic resonance/computed tomography image adapted brachytherapy (MR/CT-IABT) treated from February 2012 to July 2014. To conduct this project, we formed a working group that established the procedure and identified the indicators and benchmarks to evaluate the feasibility and safety. We considered the procedure acceptable if 90% of the indicators were consistent with the benchmarks. Magnetic resonance imaging with contrast and diffusion weighted imaging were performed with an MRI-compatible dummy applicator in the anus to define the position of the clinical target volume disease and biological information. A pre-implantation treatment planning was created in order to get information on the optimal position of the needles. Afterwards, the patient underwent a simulation CT and the definite post-implantation treatment planning was created. Results : We treated 11 patients (4 men and 7 women) with MR/CT-IABT and we performed a total of 13 procedures. The analysis of indicators for procedure evaluation showed that all indicators were in agreement with the benchmark. The dosimetric analysis resulted in a median of V 200 , V 150 , V 100 , V 90 , V 85 , respectively of 24.6%, 53.4%, 93.5%, 97.6%, and 98.7%. The median coverage index (CI) was 0.94, the median dose homogeneity index (DHI) was 0.43, the median dose non-uniformity ratio (DNR) resulted 0.56, the median overdose volume index (ODI) was 0.27. We observed no episodes of common severe acute toxicities. Conclusions : Brachytherapy is a possible option in anal cancer radiotherapy to perform the boost to complete external beam radiotherapy (EBRT). Magnetic resonance can also have biological advantages compared to the US. Our results suggest that the multiparametric MR/CT-IABT for anal cancer is feasible and safe. This new approach paves the way to prospective comparison studies between MRI and ultrasound-guided brachytherapy (USBT) in anal canal cancer.